2005
DOI: 10.1016/j.blre.2004.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of engraftment following allogeneic hematopoietic cell transplantation with reduced-intensity or nonmyeloablative conditioning

Abstract: Summary Nonmyeloablative or reduced-intensity conditioning regimens have been used to condition elderly or ill patients with hematological malignancies for allogeneic hematopoietic cell transplantation (HCT). Initial mixed donor/host chimerism (i.e. the coexistence of hematopoietic cells of host and donor origin) has been observed in most patients after such transplants. Here, we describe both factors affecting engraftment kinetics in patients given a nonmyeloablative or a reduced-intensity conditioning, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 48 publications
0
36
1
3
Order By: Relevance
“…4,11,15 Andreani et al 13 showed an 84% rejection rate in patients with thalassemia who had 425% autologous cells in WB at 2 months post transplant, and Baron et al 1,2 and Matthes-Martin et al 5 showed that low donor CD3 þ and natural killer cell chimerism at days 14 and 28 post transplant correlated with graft rejection. Long-term follow-up of patients with thalassemia showed that once tolerance to donor cells has been established, graft rejection does not occur even at low levels (o10%) of donor WB engraftment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,11,15 Andreani et al 13 showed an 84% rejection rate in patients with thalassemia who had 425% autologous cells in WB at 2 months post transplant, and Baron et al 1,2 and Matthes-Martin et al 5 showed that low donor CD3 þ and natural killer cell chimerism at days 14 and 28 post transplant correlated with graft rejection. Long-term follow-up of patients with thalassemia showed that once tolerance to donor cells has been established, graft rejection does not occur even at low levels (o10%) of donor WB engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…The study included 24 children (median age 7.6 years, range (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)) undergoing first unmodified allogeneic HSCT for a non-malignant disorder at University of California, San Francisco, (UCSF) Children's Hospital, Pediatric Blood and Marrow Transplant Unit (PBMTU) between January 2001 and March 2007. Only patients who received fludarabine-or cyclophosphamide-based conditioning regimen and had chimerism testing done by the STR technique were included.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 This choice is explained by the high level of CD34 + cells and T lymphocytes in PBSC grafts, which allows a better engraftment than BM grafts. [8][9][10][11][12] However, PBSC has also been shown to increase the risk of chronic GVHD (cGVHD) compared with BM. [13][14][15][16] Such a complication affects patients' quality of life and is associated with a higher risk of infections and death.…”
Section: Introductionmentioning
confidence: 99%